Estudantes de música: panorama geral de uma atividade de risco para a audição - Lüders, Débora (2012)
Research has shown that many musicians are unaware of the damage that loud music can bring to their professional careers, such as the difficulty in recognizing the pitch and timbre of the instruments. This study aimed to analyze the risk of hearing from music practice in undergraduate music students in the city of Curitiba, Parana. Participants included 62 students from three public institutions, 26 (41.94%) were female and 36 (58.06%) were male, aged 18-58 years (mean 26 years). Students answered a questionnaire about musical practice, hearing health history and general knowledge of the risks to hearing health, preventive measures of hearing loss, and listening habits. An audiological evaluation was performed in 42 of the 62 students and included: conventional and high frequency audiometry; transient evoked and distortion product otoacoustic emissions, and the results were compared with a control group. The sound pressure levels and frequency spectrum of musical instruments were measured. Among the students, 48.38% play stringed instruments, followed by electronic and/ or amplified instruments. 80% already have played and/ or sung for more than four years and 56% have already been part of a group for over four years; 72% study up to two hours per day, 58% rehearse three to six hours a week. Although 75% did not experience any hearing difficulties, 45% reported some auditory symptom (intolerance and/ or tinnitus). Among reported health problems were stress/ irritation, headaches, poor concentration, muscle pain, sleep problems and depression. 91.93% reported that loud music damaged hearing, 11.3% irritation or stress; 9.67% headaches and 8% tinnitus. 58% are aware of hearing protection devices, however, 80.64% of those people never use them. Compared to conventional audiometry, 39 (92.85%) of the 42 students had all hearing thresholds within normal limits. However, the worst average thresholds were observed in the left ear at all frequencies, except at 4000 Hz. When compared to the control group, the study group presented worse average hearing thresholds at frequencies of 500 Hz in the left ear, 250 Hz and 6000 Hz in both ears. Regarding the high-frequency audiometry, the worst results for the group of students occurred only at the frequency of 9,000 Hz in the right ear. However, the average threshold frequencies of 9000 Hz in the left ear and 10,000 Hz and 11,200 Hz in both ears were worse in the study group compared to the control group. There was a presence of otoacoustic emissions in 41 (97.6%) of right ears and 40 (95.2%) of the left ears. We recorded the absence of distortion product otoacoustic emissions in several students, at all frequencies, especially in the left ear. The mean DPOAE amplitudes and signal/ noise ratio were also worse in the left ear, except for at 8000 Hz Compared to the control group. It was observed that the mean amplitudes of DPOAE in the study group were lower at all frequencies, except for 4000 Hz in the right ear, and a larger number of uncertain results, especially in the left ear at all frequencies except 6000 Hz in the right ear. The average sound pressure levels encountered during academic activities varied from 77.2 dB(A) to 99.4 dB(A), with peak intensity between 78.8 dB(A) and 113.1 dB(A). The highest values occurred in symphonic band rehearsal, with higher levels in the woods section (among flutes) and the brass section, near the percussion section (tympani). From the analysis of the results, we can conclude that undergraduate students in music are at risk for hearing loss. The differences in hearing thresholds of high frequencies, if followed for a longer period of time, also associated with conventional hearing thresholds and the values of the amplitudes of otoacoustic emissions could shed light on the hearing status of musicians over the years, showing the effectiveness of early detection of hearing impairment. If this monitoring can be conducted during the school day, such as part of a Hearing Conservation Program, along with educational activities, the future musician would be much more prepared to face risky situations and, perhaps, collaborate so that the sound intensities are not strong enough to cause hearing loss, or at least that they are not exposed to the sounds for a time long enough as to affect hearing.